Faktor Risiko Bayi Berat Lahir Rendah di Rumah Sakit Umum Daerah Haji Makassar - Hatijar, Hatijar (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2020)
Low birth weight babies are babies born with a weight less than 2500 grams. LBW (low birth weight) affects the high mortality rate in infants and is at risk of experiencing obstacles in growth and development. LBW is generally caused due to lack of nutrition and nutritional needs from mother to fetus while pregnant women aged less than 20 years and more than 35 years have the risk of giving birth to LBW. The purpose of this study is to determine the risk factors that cause LBW based on maternal age and nutritional status. The research method used was observational with a cross sectional study approach. The sampling technique was random sampling at the Regional Haji Makassar General Hospital in the January to July 2015 period with a total sample of 65 people. Analysis using the Chi Square Test. The results showed that there was a relationship between maternal age, nutritional status of LBW with a value (p value = 0.00 <Î± = 0.05). Maternal age and nutritional status are factors that influence low birth weight where the results of the study indicate that there is a relationship between maternal age and nutritional status on the incidence of low birth weight. To reduce the incidence of low birth weight, it is necessary to increase counseling about the causes of low birth weight babies by health workers, especially midwives to pregnant women to prevent the risk of low birth weight birth.